Financial assessment in the state contracting processes in Colombia (2013)
Through this essay , intends to develop a study to know everything related to the enabling minimum requirements of financial capacity in the government contracting processes in Colombia, and finally achieving a greater clarity of how and which State Contracts should apply these requirements. Given the norms regulating government procurement Colombia defines a set of enabling minimum requirements of legal, financial and technical support content to the proponents which are set out in the specifications of the government contracting process, to be a filter mechanism to choose the most suitable bidders to preserve the general interest of the state; while these requirements are embedded in the Act 80 of 1993, in their application they generate many questions, because many times there isn ́t clarity for their execution. There will be a historical journey to find out how it originated the requirement of these requirements in State Contract, based in the laws, decrees and another jurisprudence that allow to have sufficient basis to develop the subject.